Importance of the left ventricular outflow tract in the need for pacemaker implantation after transcatheter aortic valve replacement. (1st August 2016) - Rodríguez-Olivares, Ramón; van Gils, Lennart; El Faquir, Nahid; Rahhab, Zouhair; Di Martino, Luigi F.M.; van Weenen, Sander; de Vries, John; Galema, Tjebbe W.; Geleijnse, Marcel L.; Budde, Ricardo P.J.; Boersma, Eric; de Jaegere, Peter P.; et al.
Abstract: Background: The interaction of left ventricular outflow tract (LVOT) and transcatheter heart valve (THV) is complex and may be device design specific. We sought to study LVOT characteristics and its relation with permanent pacemaker implantation (PPI) after transcatheter aortic valve replacement (TAVR). Methods: We studied 302 patients with a median age of 81 years [75–84]. Computed tomography was used to assess LVOT in terms of amount of calcium, perimeter and device size relative to LVOT. Results: We implanted a Medtronic CoreValve (MCS) in 203 patients, Edwards-Sapien XT (ESV-XT) in 38, Edwards-Sapien S3 (ESV-S3) in 26 and Lotus in 35 patients. Sixty-eight patients (22.5%) received a new PPI within 30 days after the index procedure. The incidence of PPI was 22.7% with MCS, 10.5% with ESV-XT, 26.9% with ESV-S3 and 31.4% with Lotus. By multivariate analysis RBBB at baseline (OR 2.9 [1.2–6.9, p = 0.014), second generation valves (OR 2.1 [1.0–4.5], p = 0.048), DOI (OR 1.20 per 1 mm increment, [1.09–1.31], p < 0.001) and LVOT sizing (OR per 1% increment 1.03 [1.01–1.07], p = 0.022) were associated with need for PPI. Sensitivity analyses suggest that a lesser degree of LVOT oversizing triggers PPI with second generation THVs vs. first generation THVs. Conclusions: More LVOT oversizing is associated with a higher need for permanent pacemaker implantation after TAVR, even more so with deeper THV implants and next generation devices (ESV-S3 and Lotus). Sizing algorithms should focus more on LVOT dimensions to reduce PPI.